Current Trends and Future Projection of HIV/AIDS Epidemic in Taiwan: A Modeling Analysis - Hsieh, Ying-Hen; Lin, Po-Chang (Current HIV Research, 2016)
Background: In the past decade, HIV/AIDS epidemic in Taiwan experienced an outbreak of HIV-1 CRF07_BC among intravenous drug users (IDU) in 2004-2006 that led to the reported HIV/AIDS case number more than doubled in less than 3 years and subsequent changes in free antiretroviral therapy (ART) treatment program for persons living with HIV/AIDS (PLWHA). Methods: We investigate HIV underreporting in Taiwan by utilizing a discrete-time compartmental mathematical model for disease transmission and HIV/AIDS surveillance data during 2001-2011. Results: The estimated underreporting ratio in 2011 is 0.45:1, down from 1:1 ratio in 2000. We also provide future projections of the numbers of reported and unreported PLWHA in Taiwan, assuming that model parameters remain unchanged in the near future. Conclusion: N-step-ahead forecasting comparison with 2012-2014 observed data indicates lower than expected number of known PLWHA and new deaths, perhaps attributable to increased treatment, but higher number of newly reported HIV/AIDS cases, which requires further investigation.
Keywords: Taiwan; projection; underreporting; reproduction number; mathematical model